2008
DOI: 10.1002/anie.200803910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclobutenes by Highly Selective Transition‐Metal‐Catalyzed Ring Expansion of Cyclopropanes

Abstract: A highly chemoselective, regioselective, and stereospecific synthesis of polysubstituted cyclobutenes, by catalyst‐controlled ring expansion of cyclopropanes via metal carbene intermediates, is reported. Transition‐metal catalysts showed profound effects on the reactivity and selectivity of metal carbene intermediates in this ring‐expansion reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 40 publications
0
48
1
Order By: Relevance
“…Based on studies from our lab 5 and others, 22,23 the regioselectivity for the cleavage of C-C σ-bonds in cyclopropanes was dependent on the stereochemistry of the cyclopropane ring, the electronic and steric properties of the substituents, and the metal catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies from our lab 5 and others, 22,23 the regioselectivity for the cleavage of C-C σ-bonds in cyclopropanes was dependent on the stereochemistry of the cyclopropane ring, the electronic and steric properties of the substituents, and the metal catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 During our search for more stable alternative cyclopropyl carbene precursors, we were attracted by the method of metal carbene formation from propargyl esters via a transition metal-catalyzed 1,2-acyloxy migration. This convenient and atom-economical 7 process was first described by Rautenstrauch in 1984, 8 and has been applied in numerous cascade reactions.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Tang and coworkers have reported a transition-metal-mediated variant in which significant improvements in the yields and selectivities were observed. 50 Several transition metal complexes were evaluated, from which AgOTf emerged as the catalyst of choice (Scheme 8.20). As can be seen in Table 8.11, a broad range of substrates (119-128) were investigated, and it was observed that this reaction is stereospecific (entries 5 and 6, Table 8.11) and regioselective (entries 7-10, Table 8.11).…”
Section: Ring Expansion Reactionsmentioning
confidence: 99%
“…The structures of B and C were proposed from spectra analyses and further confirmed by X-ray crystallography of 3 d and 4 f (see Table 2). [11] It is worth noting that for all of the type B compounds, the chemical shift of the hydrogen atom on the saturated carbon atom was less than d = 7 ppm in the H NMR spectrum. In contrast, the shift was greater than d = 7 ppm for all of the type C compounds.…”
mentioning
confidence: 91%